BICP0 Negatively Regulates TRAF6-Mediated NF-κB and Interferon Activation by Promoting K48-Linked Polyubiquitination of TRAF6 - Cao, Chong; An, Ran; Yu, YueYang; Dai, HaiYue; Qu, ZheHui; Gao, MingChun; Wang, JunWei (Frontiers in Microbiology, 2020)
The infected cell protein 0 (BICP0) is an immediate early protein encoded by BHV-1, and its RING finger domain, which endows BICP0 with intrinsic E3 ubiquitin ligase activity, is common in all ICP0 proteins. Tumor necrosis factor receptor–associated factor 6 (TRAF6) is one of the TRAF family members and is ubiquitously expressed in mammalian tissues. TRAF6 forms the MyD88-TRAF6-IRF7 complex and activates interferon induction in the TLR (Toll-like receptors) and the RLR (RIG-I-like receptor) pathway. Previous studies showed that BICP0 reduced IFN-β promoter activity by interacting with IRF7. In this study, we found that BICP0 promoted the K48-ubiquitination and degradation of TRAF6 through the ubiquitin proteasome system. The interaction between BICP0 and TRAF6 is a prerequisite for ubiquitination modification, and the 346-PAERQY-351 of BICP0 is indispensable. The motif mutation experiments showed that the tyrosine 351 of BICP0 is the key amino acid involved. Further studies demonstrated that BICP0 suppressed the NF-κB pathway via the interference of TRAF6. Moreover, degradation of TRAF6 protein influenced the K63-linked ubiquitination of IRF7 and activation of interferon promoter. Collectively, these findings indicate that the BICP0 protein suppresses the inflammation signaling and IFN production by K48-linked polyubiquitination of TRAF6 and may further clarify the immune evasion function of BICP0.